2002
DOI: 10.1097/01.wcb.0000033966.83623.7d
|View full text |Cite
|
Sign up to set email alerts
|

The Blood–Brain Barrier Creatine Transporter is a Major Pathway for Supplying Creatine to the Brain

Abstract: Summary:Although creatine plays a pivotal role in the storage of phosphate-bound energy in the brain, the source of cerebral creatine is still unclear. The authors examined the contribution made by the creatine transporter (CRT) at the blood-brain barrier in supplying creatine to the brain from blood. An in vivo intravenous administration study suggested that creatine is continuously transported from the blood to the brain against the creatine concentration gradient that exists between brain and blood. Conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
107
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 27 publications
3
107
0
Order By: Relevance
“…In brain parenchyma, SLC6A8 is expressed by neurons and oligodendrocytes. However, while SLC6A8 is also expressed by MCEC at BBB, allowing CNS to import Cr from periphery, it is absent from astrocytes, particularly from their feet lining (Braissant et al 2001b;Ohtsuki et al 2002;Tachikawa et al 2004). This raised the concept that BBB has a limited permeability for peripheral Cr, and that the brain supplies a part of its Cr by endogenous synthesis (Braissant et al 2001b;Braissant et al 2011;Braissant and Henry 2008).…”
Section: Introductionmentioning
confidence: 97%
“…In brain parenchyma, SLC6A8 is expressed by neurons and oligodendrocytes. However, while SLC6A8 is also expressed by MCEC at BBB, allowing CNS to import Cr from periphery, it is absent from astrocytes, particularly from their feet lining (Braissant et al 2001b;Ohtsuki et al 2002;Tachikawa et al 2004). This raised the concept that BBB has a limited permeability for peripheral Cr, and that the brain supplies a part of its Cr by endogenous synthesis (Braissant et al 2001b;Braissant et al 2011;Braissant and Henry 2008).…”
Section: Introductionmentioning
confidence: 97%
“…10,47,73,74) Nevertheless, the retina is especially differentiated for vision. This prompts the hypothesis that the inner BRB expresses different molecules than the BBB.…”
Section: Cell-to-cell Interactions and Differencesmentioning
confidence: 99%
“…12,13) The CRT cDNA fragment was amplified by RT-PCR from TM-BBB cells possibly due to the similarity in the nucleotide sequence between CRT and neurotransmitter transporters. 5) Furthermore, TM-BBB cells exhibited creatine uptake which is significantly inhibited by CRT inhibitors, such as b-guanidinopropionate and guanidinoacetate. Our immunohistochemical analysis revealed that there is intense expression of CRT in mouse BCECs (Fig.…”
mentioning
confidence: 99%
“…1). 5) Creatine plays a key role in this energy-storing process. The phosphate-bound energy of ATP is transferred to creatine and stored as phosphocreatine to regenerate ATP from ADP ( Fig.…”
mentioning
confidence: 99%